Product variety and technical change - Richard Frensch; Vitalija Gaucaite-Wittich (Osteuropa-Institut München, 2006)
Several trade-based measures of product variety have recently been used implicitly to represent states of technology, promoting long-run growth. In this paper, we define the state of technology as the range of specialised production processes and propose the variety of capital goods available for production as a direct measure of technology. Within a simple growth framework, we derive a testable conditional technological convergence hypothesis on this measure. The hypothesis is tested with highly disaggregated trade data by economic categories, using tools from the income convergence literature. The results suggest that trade-based count measures of the variety of available capital goods indeed behave as if they were representing technology and that there is conditional technological convergence among our panel of mainly OECD and transition economies.
Keywords: F14; O33; 330; Product variety; diffusion; adoption; technical change; Produktdifferenzierung; Investitionsgut; Technologie; Außenhandelsstruktur; Innovationsdiffusion; Technischer Fortschritt; Entwicklungskonvergenz; OECD-Staaten; Osteuropa